ORIENTASI EKOTEOLOGI DALAM KEPEMIMPINAN PENDIDIKAN ISLAM - Siswadi, Siswadi (STKIP Pesisir Selatan, 2026)
This study aims to examine the eco-theological orientation in Islamic educational leadership as a normative response to the contemporary ecological crisis. Drawing on key Islamic concepts such as khalifah, amanah, ihsan, mizan, and the prohibition against fasad, this study seeks to formulate a leadership framework that positions ecological concern as an integral part of the educational mission of Islamic educational institutions. The study employs a qualitative approach using library research to examine books, journal articles, policy documents, and Islamic literature related to Islamic educational leadership, Islamic eco-theology, environmental education, and sustainable education, analyzed through content analysis and thematic synthesis. The findings indicate that an eco-theological orientation can be integrated into Islamic educational leadership through the refinement of vision and mission, the development of an environmentally friendly curriculum and school culture, and the exemplary role of leaders as agents of ecological change; this article offers conceptual principles of eco-theologically oriented Islamic educational leadership as a foundation for the development of policies and institutional practices in schools and madrasahs.